Khao Mo: Mythical Escapism - Pradittasnee, Sanitas (Nakhara : Journal of Environmental Design and Planning, 2016)
Khao Mo - (Mythical Escapism)” originated from the exhibition, “Resort: An Art Exhibition for Landscape of Rest at BACC. “Khao Mo” tries to transfer human belief and expression from the past through the present. When the time passes, the unifying ideal of nature and religion gradually becomes the identity of idea and expression.